Effects of elevated atmospheric [ CO 2 ] on instantaneous transpiration efficiency at leaf and canopy scales in E ucalyptus saligna - Craig V.M. Barton; Remko A. Duursma; Belinda E. Medlyn; David S. Ellsworth; Derek Eamus; David T. Tissue; Mark A. Adams; Jann Conroy; Kristine Y. Crous; Marion Liberloo; Markus Löw; Sune Linder; et al. (Global Change Biology, 2012)
Rising atmospheric concentrations of CO 2 ( C a ) can reduce stomatal conductance and transpiration rate in trees, but the magnitude of this effect varies considerably among experiments. The theory of optimal stomatal behaviour predicts that the ratio of photosynthesis to transpiration (instantaneous transpiration efficiency, ITE ) should increase in proportion to C a . We hypothesized that plants regulate stomatal conductance optimally in response to rising C a . We tested this hypothesis with data from young Eucalyptus saligna Sm. trees grown in 12 climate‐controlled whole‐tree chambers for 2 years at ambient and elevated C a . Elevated C a was ambient + 240 ppm, 60% higher than ambient C a . Leaf‐scale gas exchange was measured throughout the second year of the study and leaf‐scale ITE increased by 60% under elevated C a , as predicted. Values of leaf‐scale ITE depended strongly on vapour pressure deficit ( D ) in both CO 2 treatments. Whole‐canopy CO 2 and H 2 O fluxes were also monitored continuously for each chamber throughout the second year. There were small differences in D between C a treatments, which had important effects on values of canopy‐scale ITE . However, when C a treatments were compared at the same D , canopy‐scale ITE was consistently increased by 60%, again as predicted. Importantly, leaf and canopy‐scale ITE were not significantly different, indicating that ITE was not scale‐dependent. Observed changes in transpiration rate could be explained on the basis that ITE increased in proportion to C a . The effect of elevated C a on photosynthesis increased with rising D . At high D , C a had a large effect on photosynthesis and a small effect on transpiration rate. At low D , in contrast, there was a small effect of C a on photosynthesis, but a much larger effect on transpiration rate. If shown to be a general response, the proportionality of ITE with C a will allow us to predict the effects of C a on transpiration rate.

Carbon-based secondary metabolites and internal nitrogen pools in Populus nigra under Free Air CO2 Enrichment (FACE) and nitrogen fertilisation - Zhi-Bin Luo; Carlo Calfapietra; Giuseppe Scarascia-Mugnozza; Marion Liberloo; Andrea Polle (Plant and Soil, 2008)

Woody biomass production during the second rotation of a bio‐energy Populus plantation increases in a future high CO 2 world - MARION LIBERLOO; CARLO CALFAPIETRA; MARTIN LUKAC; DOUGLAS GODBOLD; ZHI‐BIN LUO; ANDREA POLLE; MARCEL R. HOOSBEEK; OLEVI KULL; MICHAL MAREK; CHRISTINE RAINES; MAURO RUBINO; GAIL TAYLOR; et al. (Global Change Biology, 2006)
The quickly rising atmospheric carbon dioxide (CO 2 )‐levels, justify the need to explore all carbon (C) sequestration possibilities that might mitigate the current CO 2 increase. Here, we report the likely impact of future increases in atmospheric CO 2 on woody biomass production of three poplar species ( Populus alba L. clone 2AS‐11, Populus nigra L. clone Jean Pourtet and Populus × euramericana clone I‐214). Trees were growing in a high‐density coppice plantation during the second rotation (i.e., regrowth after coppice; 2002–2004; POPFACE/EUROFACE). Six plots were studied, half of which were continuously fumigated with CO 2 (FACE; free air carbon dioxide enrichment of 550 ppm). Half of each plot was fertilized to study the interaction between CO 2 and nutrient fertilization. At the end of the second rotation, selective above‐ and belowground harvests were performed to estimate the productivity of this bio‐energy plantation. Fertilization did not affect growth of the poplar trees, which was likely because of the high rates of fertilization during the previous agricultural land use. In contrast, elevated CO 2 enhanced biomass production by up to 29%, and this stimulation did not differ between above‐ and belowground parts. The increased initial stump size resulting from elevated CO 2 during the first rotation (1999–2001) could not solely explain the observed final biomass increase. The larger leaf area index after canopy closure and the absence of any major photosynthetic acclimation after 6 years of fumigation caused the sustained CO 2 ‐induced biomass increase after coppice. These results suggest that, under future CO 2 concentrations, managed poplar coppice systems may exhibit higher potential for C sequestration and, thus, help mitigate climate change when used as a source of C‐neutral energy.

Carbon partitioning to mobile and structural fractions in poplar wood under elevated CO 2 (EUROFACE) and N fertilization - ZHI‐BIN LUO; CARLO CALFAPIETRA; MARION LIBERLOO; GIUSEPPE SCARASCIA‐MUGNOZZA; ANDREA POLLE (Global Change Biology, 2006)
To determine whether globally increasing atmospheric carbon dioxide (CO 2 ) concentrations can affect carbon partitioning between nonstructural and structural carbon pools in agroforestry plantations, Populus nigra was grown in ambient air (about 370 μmol mol −1 CO 2 ) and in air with elevated CO 2 concentrations (about 550 μmol mol −1 CO 2 ) using free‐air CO 2 enrichment (FACE) technology. FACE was maintained for 5 years. After three growing seasons, the plantation was coppiced and one half of each experimental plot was fertilized with nitrogen. Carbon concentrations and stocks were measured in secondary sprouts in seasons of active growth and dormancy during 2 years after coppicing. Although FACE, N fertilization and season had significant tissue‐specific effects on carbon partitioning to the fractions of structural carbon, soluble sugars and starch as well as to residual soluble carbon, the overall magnitude of these shifts was small. The major effect of FACE and N fertilization was on cell wall biomass production, resulting in about 30% increased above ground stocks of both mobile and immobile carbon pools compared with fertilized trees under ambient CO 2 . Relative C partitioning between mobile and immobile C pools was not significantly affected by FACE or N fertilization. These data demonstrate high metabolic flexibility of P. nigra to maintain C‐homeostasis under changing environmental conditions and illustrate that nonstructural carbon compounds can be utilized more rapidly for structural growth under elevated atmospheric [CO 2 ] in fertilized agroforestry systems. Thus, structural biomass production on abandoned agricultural land may contribute to achieving the goals of the Kyoto protocol.